FEAR OF MISSING OUT (FOMO) DAN LINGKUNGAN TEMAN SEBAYA SEBAGAI FAKTOR DALAM HIGHER EDUCATION CHOICE - Muhamad Ahbab; Sukadi; Sri Rahayu (SUKMA: Jurnal Pendidikan, 2025)
The decision to pursue higher education is an important choice that affects both a student’s career and the quality of human resources in a country. Higher education participation in Indonesia remains low, with a Gross Enrollment Rate (GER) of 31.45% in 2022, far from the government’s target of 50% by 2045. This study aims to: (1) describe the levels of Fear of Missing Out (FoMO), peer environment, and students’ decisions to continue their studies, and (2) analyze the influence of FoMO and peer environment on academic decision-making. The research employed a quantitative ex post facto method, collecting data through questionnaires distributed to 166 students from the Building Engineering Education, Civil Engineering, Architecture Education, and Architecture programs at Universitas Pendidikan Indonesia. Data were analyzed using IBM SPSS 25.0. The results indicate that FoMO and peer environment levels were in the strong category, while the decision to continue studies was very strong. Regression analysis shows that both FoMO and peer environment significantly influence students’ decisions, with peer environment exerting a more dominant effect. These findings highlight the importance of balancing digital social pressures with real-life social support in guiding students’ educational choices.